PB1-F2 Peptide Derived from Avian Influenza A Virus H7N9 Induces Inflammation via Activation of the NLRP3 Inflammasome - Pinar, Anita (J Biol Chem, 2017)
The emergence of avian H7N9 influenza A virus in humans with associated high mortality has highlighted the threat of a potential pandemic. Fatal H7N9 infections are characterized by hyperinflammation and increased cellular infiltrates in the lung. Currently there are limited therapies to address the pathologies associated with H7N9 infection and the virulence factors that contribute to these pathologies. We have found that PB1-F2 derived from H7N9 activates the NLRP3 inflammasome and induces lung inflammation and cellular recruitment that is NLRP3-dependent. We have also shown that H7N9 and A/Puerto Rico/H1N1 (PR8)PB1-F2 peptide treatment induces significant mitochondrial reactive oxygen production, which contributes to NLRP3 activation. Importantly, treatment of cells or mice with the specific NLRP3 inhibitor MCC950 significantly reduces IL-1β maturation, lung cellular recruitment, and cytokine production. Together, these results suggest that PB1-F2 from H7N9 avian influenza A virus may be a major contributory factor to disease pathophysiology and excessive inflammation characteristic of clinical infections and that targeting the NLRP3 inflammasome may be an effective means to reduce the inflammatory burden associated with H7N9 infections.